“Determinación de curvas de extracción de nutrientes N-P-K con la aplicación de fertilización en el cultivo de cebolla china (allium fistolosum L.) bajo condiciones del distrito de Caynarachi” - Castillo García, Banny Niels (2016)
The research was conducted in 2014 in the District of Caynarachi, Lamas province, San Martín region, geographically located 06º 19' 49.52" south latitude and 76 º 17' 6.19" latitude west with a 187 msnmm altitude. The work was to "determine the curves of extraction of nutrients N - P - K fertilizer application in the cultivation of Chinese onion (Allium fistolosum L.) Under District Caynarachi" Evaluations were made fresh and dry weight of bulbs and leaves for treatments at 1 O, 20, 30 and 60 days, foliar chemical analysis of bulbs and leaves in which the percentages of nitrogen, phosphorus and potassium were determined performed. Extraction curves macronutrients ( N, P, K ) per treatment (TO, T1, T2, T3 ), these being (O - O - O), (85 - 50-160 ), ( 100-70 - 200 ), (150 - 90 - 240); and then make the total extraction of macronutrients by treatment expressed in kg I ha . The design was completely randomized with 4 treatments and 3 comments. The variables evaluated and statistically analyzed were fresh leaf dry weight per treatment and dry bulbs, fresh weight and (TO, T1 , T2 , T3) 1 independently in each evaluation period (10, 20, 30 and 60) days, plant tissue analysis and leaves both bulbs ( N, P, K ). In the accumulated nutrient removal for all treatments (TO, T1, T2 and T3), Potassium macronutrient ( K ) is the extracted feature therefore this element is fundamental in the development of the crop being the most extracted by the plant.